From Ideas to Action: Empowering Youth as Future Business Leaders in Entrepreneurship - Monica Potu; Janice C. Siahaya; Oliandes Sondakh (Universitas Pelita Harapan, 2025)
One form of the tridharma of higher education is carrying out Community Service (PKM). The UPH Surabaya campus Management study program conducts PKM in the form of an entrepreneurship workshop. This workshop, which is applied in community service, aims to increase the confidence of class X students to try new things and become entrepreneurs from an early age. This activity is designed to provide an in-depth understanding of the principles of becoming a true entrepreneur as well as training practical skills that can be directly applied in entrepreneurial activities. Through a participatory approach, participants are expected to be able to produce simple products with limited resources, and even promote the results of their business in an interesting way. The expected result is an increase in the capacity of participants who can then become young entrepreneurs who participate in efforts to boost the Indonesian economy in the future.